2020
DOI: 10.1186/s13229-020-00351-4
|View full text |Cite
|
Sign up to set email alerts
|

Cortical neurons derived from human pluripotent stem cells lacking FMRP display altered spontaneous firing patterns

Abstract: Background: Fragile X syndrome (FXS), a neurodevelopmental disorder, is a leading monogenetic cause of intellectual disability and autism spectrum disorder. Notwithstanding the extensive studies using rodent and other pre-clinical models of FXS, which have provided detailed mechanistic insights into the pathophysiology of this disorder, it is only relatively recently that human stem cell-derived neurons have been employed as a model system to further our understanding of the pathophysiological events that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 59 publications
3
29
1
Order By: Relevance
“…However, differentiation of FX-PSCs led to poor neuronal maturation and decreased spike frequencies relative to control neurons [16,17]. Nevertheless, other studies demonstrated inconsistent results regarding the functional differences between FX-PSCs and control neurons [18][19][20]. In the current study, hESC isogenic subclones were generated, one with a full FX mutation and one that is free of the mutation (WT) but shares the same genetic background, enabling us to overcome variability between lines.…”
Section: Introductionmentioning
confidence: 90%
“…However, differentiation of FX-PSCs led to poor neuronal maturation and decreased spike frequencies relative to control neurons [16,17]. Nevertheless, other studies demonstrated inconsistent results regarding the functional differences between FX-PSCs and control neurons [18][19][20]. In the current study, hESC isogenic subclones were generated, one with a full FX mutation and one that is free of the mutation (WT) but shares the same genetic background, enabling us to overcome variability between lines.…”
Section: Introductionmentioning
confidence: 90%
“…It is likely that the observed reduction in ADBE reflects a compensatory or homeostatic mechanism to counteract the increased excitability in FXS and Fmr1 KO models (Booker et al, 2019; Das Sharma et al, 2020; Zhang et al, 2014). BK channel openers decrease hyperexcitability in Fmr1 KO models both in vitro and in vivo by increasing hyperpolarization, resulting in decreased calcium influx in nerve terminals.…”
Section: Resultsmentioning
confidence: 99%
“…A homeostatic reduction in ADBE in response to increased hyperexcitability would not be a homogenous adaptation across the brain, since neurons that display high firing rates would be disproportionately impacted. Therefore, even if reduced ADBE is not a causal mechanism in FXS, it may still be a valuable therapeutic intervention point to correct hyperexcitability in specific circuits (Booker et al, 2019; Das Sharma et al, 2020). Future studies are now required to determine whether modulation of ADBE can sculpt circuit activity in FXS (and other autism models that display hyperexcitability - such as SynGAP haploinsufficiency disorder (Gamache et al, 2020)).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations